Dinâmica espaço-temporal de transições floresta de galeria-campo limpo e as relações florísticas e estruturais entre borda e interior - Coelho, Gabriela Aparecida de Oliveira (2015)
The goal with this research was to identify spatial and temporal patterns in the dynamics of shrubs and trees in natural edges of gallery forests as well as floristic-structural relationships between the edge and interior communities of these forests. In the dynamics research were evaluated annually (2009-2013) nine edge communities in 15×20 m plots, 3 plots in each study area. All individuals with DBH ≥ 1 cm were identified, mapped, measured (DBH) and their total height estimated. In annual inventories, the survivors were remeasured, the dead were computed and the recruits included in the sampling. Most sites (except the ones where fire occurred) had higher recruitment than mortality, resulting in density increase inside the edge and reflecting an expansion of forests on surrounding grassland. The rates of dynamics had little variation among the study sites and large variation among the intervals, showing strong influence of the climate that, combined with fire events, seems to control the dynamics of these transitions. For the evaluation of the relationship between species composition and community structure comparing forest edges and interior, were allocated in 2013 three plots of 10 × 20 m, 30 meters away from the edge, towards the interior, in eight of the sites previously sampled for the study of edge dynamics. The inclusion criteria and sampling were the same as those used for the edge. The species richness differed between edge and interior environments for the total sample, but within each community were found differences only for two sites. The values of Shannon (H') did not differ between the edge and the interior, neither for the total sample nor within each forest. There were no differences in the density of individuals between the edge and the interior and, although the basal area has been shown to be different in the total sample, were found only for two study sites significant differences for basal area. Evaluating forests separately, the edges were more heterogeneous than the interior because were found significant differences for both density and the basal area for the edge, while in the interior only the density differed. Edge and interior area differed in the frequency of the individuals at size classes, wherein the edge had more small individuals than interior, where the frequency in the remaining size classes was larger. The plots tended to cluster by environment, indicating a low floristic similarity between edges and interior. Edaphic variables were more important in the edges and in the interior, topographical variables explained more floristic variation.